Enhanced reliability assessment of punching shear resistance models for flat slabs without shear reinforcement. (1st January 2021) - Ricker, Marcus; Feiri, Tânia; Nille-Hauf, Konstantin; Adam, Viviane; Hegger, Josef
Highlights: Reliability assessment of punching shear capacity for? flat slabs without shear reinf. Stochastic modelling of the random variables in the punching shear resistance function. Safety level assessment of the resistance model and comparison to EN 1990 ( β = 3.8). Abstract: Punching shear is one of the main failure mechanisms in flat slabs. To prevent such failures, modern structural codes, as EN 1992-1-1, offer design provisions against punching shear. However, these provisions were calibrated based on experience, which can affect the precision of the resulting safety level. The use of modern reliability analysis techniques is required for a more precise evaluation of the safety level of these structural systems. This paper presents a comprehensive review of the state-of-the-art of reliability techniques where the safety level of design provisions for punching shear resistance without shear reinforcement is investigated. This study addresses three reliability analysis techniques: Mean-Value First Order Second Moment Method (MVFOSM), First-Order Second Moment Method (FOSM) and a Monte-Carlo simulation with Importance Sampling (MC-IS). Reliability indices β are used as a practical measurement of the safety level representing probabilities of failure. The parameters influencing the punching shear capacity without shear reinforcement were varied that the area of practical interest is covered. The estimated reliability indices β are evaluated and compared to a target safety level given by EN 1990 for a 50-year reference period where β is equal to 3.8. The results seem to confirm that the punching shear provisions for slabs without shear reinforcement according to EN 1992-1-1 achieve a required safety level, which is in accordance to the target level given by EN 1990. In addition, the study shows that the use of the techniques FOSM and MC-IS seems appropriate for determining the probability of failure of the design equation for the punching shear capacity without shear reinforcement. Furthermore, the study suggests that the method MVFOSM may not be suitable to assess the absolute safety level of such design equations. Finally, the study highlights the potential of using the aforementioned reliability analysis techniques and stresses the importance of modelling the uncertainties for a precise structural safety assessment of flat slabs without shear reinforcement.